The Effect Of Problem-Based Learning Model Assisted By Live Worksheets On Students' Mathematical Reasoning Ability - Sofia Rengganis Santosa; Ervin Azhar (International Journal of Research in Education, 2025)
This study aims to determine the effects of using the problem-based learning (PBL) model and live worksheet media on students' mathematical reasoning skills.  The research method used was quantitative and quasi-experimental.  The study included all Grade X students from a private high school in Jakarta who had relatively balanced math skills.  The study sample comprised four classes (X.1, X.2, X.4, and X.6), which were randomly selected using random sampling technique and each received a different learning treatment; X.1 was taught using the TCL method with PPT, X.2 received PBL with PPT, X.4 received PBL assisted by Live Worksheets, and X.6 was taught using the TCL method assisted by Live Worksheets.  A descriptive test, validated and pre-tested by experts, served as the instrument. The results of the ATS showed that there were no significant differences in the initial abilities between the classes.  A mathematical reasoning ability test was conducted after the treatment and the data analysis was performed using non-parametric tests, as the data did not meet the requirements of parametric tests.  The test results yielded an Asymp. Sig value of 0.000 <0.05, which implies the rejection of H0. This means that there is a difference in the students' mathematical reasoning ability between the four classes.  The class that applied the PBL and live worksheet model achieved the best average result. This indicates that the combination of these methods effectively improves students' mathematical thinking ability.